Caves and their fauna in Highlands and Escarpments of Angola and Namibia - Matos, Daniela de (2023)
Several landscapes in the highlands and escarpments of Angola and Namibia (HEAN) have karstic regions with caves. Within the Northern Escarpment in Angola there are two main karstic regions. The first one includes the northern caves associated with a tropical climate and mostly concentrated in Ambuíla, Uíge Province. The second region comprises caves near the Atlantic coast, which are linked to underground flows of the Cambongo-Negunza River. An additional cluster of caves is on the Humpata Plateau and its edges within Angola’s Marginal Mountain Chain landscape. Most caves in Namibia are in the Karstveld and Khomas Hochland Plateau landscapes in karstic areas of relatively high rainfall. In this paper, we provide a brief overview of the history of cave exploration, sites and fauna documented in them. We report on the fauna recorded during surveys in 2010 and 2018–2021 in the southern karst around Humpata, Huíla Province; and summarise information available on fauna from Namibia. Most species recorded in Angolan caves are trogloxene taxa observed or collected in cave sediments. Namibian caves house a diversity of invertebrates, many of which are endemic or likely to be endemic to Namibia and the HEAN. Two endemic fish in underground lakes in Namibia are critically endangered. This study emphasises the need for further field research and for strategies to conserve caves and their faunas in both countries.